An open sandwich immunoassay for detection of 13(R, S)-hydroxy-9(E), 11(E)-octadecadienoic acid. Issue 5 (1st February 2017) - Dong, Jinhua; Shichiri, Mototada; Chung, Chan-I.; Shibata, Takahiro; Uchida, Koji; Hagihara, Yoshihisa; Yoshida, Yasukazu; Ueda, Hiroshi
Abstract : Lipid peroxidation is involved in many disorders and diseases such as cardiovascular disease, cancers, neurodegenerative diseases, and even aging. Abstract : Lipid peroxidation is involved in many disorders and diseases such as cardiovascular disease, cancers, neurodegenerative diseases, and even aging. Lipid peroxidation products existing in blood or bodily fluids are very important biomarkers for the diagnosis of such diseases. In particular, 13( R, S )-hydroxy-9( E ), 11( E )-octadecadienoic acid (13-( E, E )-HODE) is an oxidiation product of linoleic acid, which is an important biomarker for many diseases such as diabetes and Alzheimer's disease. In this study, we successfully displayed the antigen-binding fragment of an antibody produced by hybridoma 1213-1 on the M13 phage and performed analysis of the antibody variable region genes. The blast results suggested that it is a novel antibody. We also developed a phage-antibody-based competitive ELISA and a novel Open Sandwich ELISA (OS ELISA) for the detection of 13-( E, E )-HODE. The OS ELISA showed a limit of detection (LOD) of 15.6 nM of 13-( E, E )-HODE and low cross-reactivity with other HODE such as 9-( E, E )-HODE. Another format of the open sandwich ELISA with purified maltose binding protein-fused VL and VH -phage showed a lower LOD of 2.2 nM of 13-( E, E )-HODE, which may be sensitive enough to detect the concentration of 13-( E, E )-HODE in patients' blood samples. This is the first OS ELISA for the detection of lipids, and we believe it also represents the first molecular cloning of anti -HODE antibody genes.